Implementasi Akuntansi Pura: Studi Kasus di Pura Khayangan Tiga Desa, Kamiwangi, Kecamatan Toili Barat, Kabupaten Banggai, Provinsi Sulawesi Tengah - Ni Nyoman Dina Anjani; Rio Monoarfa; Usman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to implement accounting in the preparation of financial reports at Khayangan Tiga Temple, Kamiwangi Village in accordance with Accounting Standards, especially ISAK 35. This research uses a qualitative approach with descriptive methods. The informants in this study were 5 people. In this research, data was collected using observation, interview and documentation techniques. The data analysis techniques in this research are data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that Pura Khayangan Tiga, Kamiwangi Village, has carried out financial records, but it is still done in a simple manner where it is only limited to cash income and expenditure. The financial reports presented are only daily cash reports which are still not in accordance with the Financial Accounting Standards Interpretation (ISAK) No. 35. After presenting the financial report for Khayangan Temple Three Kamiwangi Villages based on ISAK No. 35 produces five financial reports, namely Comprehensive Income Report, Change in Net Assets Report, Financial Position Report, Cash Flow Report, and Notes to Financial Reports.